PENERAPAN METODE DISKUSI BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS XI IPS 1 - Musa’adah Baroroh; Bambang Suyadi (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2016)
This research is a classroom action research (CAR) in order to increase student’s learning activity and outcomes of class XI IPS 1 in SMA Plus Al-Azhar Jember on the basic competence of identifying the benefit and factor that affects the internasional trade through discussion method application assisted by audio-visual media. This research consists of four stages that is planning, action, observation, and reflection. Using purposive area method to determine the research location in SMA Plus Al-Azhar Jember of class XI IPS 1. The research subject of this research is all of students in class XI IPS 1 amount to 28 students consists of 15 male students and 13 female students. This research was using observation, interview, and test and documentation to collect the research data. The data analysis of students’ learning activity derived from the observation when the observer did the action stage. Whereas, students’ learning outcomes analysis was acquired from the post-test. The result of this research shows that the application of discussion method assisted by audio-visual media in learning process can increase students’ learning activity from active category in cycle 1 go through with very active category in cycle 2 with percentage of 68% up to 83% as well as the students’ learning outcomes. The students’ average score in cycle 1 was 75,9 then increase up to 79,04 in cycle 2. Meanwhile, for the classically success was increasing from 74% in cycle 1 up to 93% in cycle 2. So that, based on the data analysis this research can prove that students’ learning activity and outcomes can be increased by applying discussion method assisted by audio-visual media.